Legal Politics to Build a State of Happiness: An Idea in a State Based on the 1945 Constitution - Panjaitan, Marojahan JS (International Journal of Criminology and Sociology, 2021)
This research was conducted with the intent and purpose of answering two problem formulations, namely: what caused Indonesia to lag behind other countries, and secondly, how the legal politics in developing a country of happiness in Indonesia. The research method uses the method of legislation approach and comparison with literature studies. Based on research, several factors that cause Indonesia to lag behind other countries, namely: convoluted bureaucratic culture, a state administration that is not responsive to the needs of society, a national education system that is unable to produce quality graduates, unstable political conditions, Corruption, Collusion, and Nepotism are rife, and the development of primordial identity politics. Legal politics in developing a state of happiness is based on the purpose of a state based on the 1945 Constitution, namely: realizing a state of happiness. That is the idea of a state that must be realized in the life of the state in Indonesia which is mandated by the country’s founders. Various efforts have been made in realizing this, but until now have not given satisfactory results. Indonesia is still far behind other countries. Of the 156 happiest countries chosen, Indonesia ranks 92. That means the government has not succeeded in giving happiness to its people.